The role of the assessment policy in the relation between learning and performance. Issue 3 (11th December 2017) - Kickert, Rob; Stegers‐Jager, Karen M; Meeuwisse, Marieke; Prinzie, Peter; Arends, Lidia R
Abstract : Context: Optimising student learning and academic performance is a continuous challenge for medical schools. The assessment policy may influence both learning and performance. Previously, the joint contribution of self‐regulated learning (SRL) and participation in scheduled learning activities towards academic performance has been reported. However, little is known about the relationships between SRL, participation and academic performance under different assessment policies. Objectives: The goal of this study was to investigate differences in average scores of SRL, participation and academic performance of students under two assessment policies: (i) a conjunctive lower stakes, lower performance standard (old) assessment policy and (ii) a compensatory higher stakes, higher performance standard (new) assessment policy. In addition, this research investigated whether the relationships between academic performance, SRL and participation are similar across both assessment policies. Methods: Year‐1 medical students (i) under the old assessment policy ( n = 648) and (ii) under the new assessment policy ( n = 529) completed the Motivated Strategies for Learning Questionnaire on SRL, and additional items on participation. Year‐1 performance was operationalised as students' average Year‐1 course examination grades.manova and structural equation modelling were used for analyses. Results: Generally, students under the new assessment policy showed significantly higher Year‐1 performance, SRL and participation, compared with students under the old assessment policy. The relationships between Year‐1 performance, SRL and participation were similar across assessment policies. Conclusions: This study indicates that the higher academic performance under a compensatory higher stakes, higher performance standard assessment policy, results from higher SRL and participation, but not from altered relationships between SRL, participation and performance. In sum, assessment policies have the potential to optimise student learning and performance. Abstract : This study indicates that student learning and performance are sensitive to changes in characteristics of the assessment policy, such as higher stakes and higher performance standards.